2016
DOI: 10.1136/jech-2015-206760
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle changes at middle age and mortality: a population-based prospective cohort study

Abstract: NCT00119912; pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
15
2
3
Order By: Relevance
“…In the Norwegian  Colorectal Cancer Prevention colorectal screening trial, a one unhealthy behaviour decrease was associated with a larger effect on mortality (HR 0.62) than those found in the current study (HR 0.93) and exclusion of people reporting chronic disease or severe pain did not attenuate this estimate 10. The attenuation we observed after excluding a more comprehensive range of diagnoses suggests that poor physical health may prompt both the adoption of an unhealthy lifestyle and increase the risk of mortality.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In the Norwegian  Colorectal Cancer Prevention colorectal screening trial, a one unhealthy behaviour decrease was associated with a larger effect on mortality (HR 0.62) than those found in the current study (HR 0.93) and exclusion of people reporting chronic disease or severe pain did not attenuate this estimate 10. The attenuation we observed after excluding a more comprehensive range of diagnoses suggests that poor physical health may prompt both the adoption of an unhealthy lifestyle and increase the risk of mortality.…”
Section: Discussioncontrasting
confidence: 78%
“…Reductions in mortality risk have been associated with smoking cessation,5 increases in physical activity6 7 and fruit consumption,7 8 but very few studies have examined changes in these behaviours combined. Of the two studies, one cohort study,9 and an analysis based on the control arm of a randomised colorectal screening trial,10 found that unhealthy changes in lifestyle (body mass index (BMI) <30 kg/m 2 ; non-smoking, physically active and a healthy diet) were associated with increases in mortality risk. For healthy changes, one study found the risk of mortality improved,10 whereas the other did not 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent negative lifestyles consisting of multiple negative HRBs during mid-life have been found to be associated with earlier mortality (15), whilst positive change in HRBs during midadulthood appears to reduce the risk of premature death (15), improve physical functioning (16) and protect against disability in later life (5). Moreover, understanding how HRB cluster membership changes over time can inform the development of more effective interventions that target multiple negative HRBs (17,18).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Mereka akan membuat perubahan kepada aspek dan gaya hidup yang dirasakan tidak sesuai untuk mencapai kesejahteraan hidup. Berstad et al (2016) telah meninjau kesan perubahan gaya hidup ke atas kadar kematian dalam kalangan dewasa pertengahan usia berumur antara 50 hingga 60 tahun. Kajian mendapati bahawa dewasa pertengahan usia yang membuat perubahan gaya hidup ke arah yang lebih positif (berdasarkan saranan doktor) mempunyai jangka hayat yang lebih panjang dan dapat mengelakkan daripada kematian awal (Berstad et al 2016).…”
Section: Pengenalanunclassified